A Novel Choice to Correct Inflammation-Induced Anemia in CKD: Oral Hypoxia-Inducible Factor Prolyl Hydroxylase Inhibitor Roxadustat - Yan, Zhipeng; Xu, Gaosi (Frontiers in Medicine, 2020)
Anemia is a complication of chronic kidney disease (CKD), primarily due to insufficient secretion of erythropoietin (EPO) by the kidney. Erythropoiesis-stimulating agents (ESAs) are used to treat anemia associated with chronic kidney disease. A poor response to ESAs has been associated with inflammation. Inflammation can affect erythrocytes and its production in many ways, but mainly through the inflammatory cytokine IL-6 to stimulate the synthesis of hepcidin in the liver. Hepcidin causes iron insuffienciency, which causes erythrocytes to fail to mature normally. In addition, inhibition of bone marrow erythroid precursor cells by inflammatory cytokines such as IL-1 and TNF‐α also affects bone marrow hematopoiesis. These cytokines are also important factors leading to EPO resistance. Roxadustat is a new drug for the treatment of renal anemia. In addition to promoting the production of EPO, clinical trials have shown that it can significantly reduce hepcidin and can potentially be used for the treatment of inflammation-induced anemia in CKD.